2023
DOI: 10.1111/apha.14013
|View full text |Cite
|
Sign up to set email alerts
|

The effects of menstrual cycle phases on immune function and inflammation at rest and after acute exercise: A systematic review and meta‐analysis

Abstract: The immune system plays an important role in mediating exercise responses and adaptations. However, whether fluctuating hormone concentrations across the menstrual cycle may impact these processes remains unknown. The aim of this systematic review with meta‐analysis was to compare baseline concentrations as well as exercise‐induced changes in immune and inflammatory parameters between menstrual cycle phases. A systematic literature search was conducted according to the PRISMA guidelines using Pubmed/MEDLINE, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 220 publications
(273 reference statements)
0
3
0
Order By: Relevance
“…17 Over the course of a month, the female body is exposed to hormone fluctuations, which represents yet another variable that influences muscle physiology. 18 Differences in fibre composition are accompanied by differences in neuromuscular properties. Consequently, neuromuscular recruitment differs between sexes.…”
Section: Sexesmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Over the course of a month, the female body is exposed to hormone fluctuations, which represents yet another variable that influences muscle physiology. 18 Differences in fibre composition are accompanied by differences in neuromuscular properties. Consequently, neuromuscular recruitment differs between sexes.…”
Section: Sexesmentioning
confidence: 99%
“…In the context of chronophysiology, it is even suggested that the timing of exercise during the day might influence the impact of exercise‐induced adaptations 17 . Over the course of a month, the female body is exposed to hormone fluctuations, which represents yet another variable that influences muscle physiology 18 …”
Section: Balance Differs Between Sexesmentioning
confidence: 99%
“…The follicular phase predominantly exerts anti-inflammatory effects, while the luteal phase is associated with pro-inflammatory responses, influencing basal immune functioning and contributing to cytokine expression dynamics [40]. Studies investigating serum cytokines such as IL-1β, IL-8, and IFN-γ have generally found no difference between the follicular and luteal phases [41][42][43]. Our result also showed that sCD14, sCD163, and MIF levels do not vary significantly with the menstrual cycle phase among infertile women.…”
Section: Soluble Cd14 Cd163 and Mif In Endometriosismentioning
confidence: 99%